WiMAX handbook : - Ohrtman, Frank (McGraw-Hill, 2005)
Wi-MAX is a big deal because it’s cheaper, smaller, simpler and easier to use than any existing broadband option (DSL, cable, fiber, 3G wireless) – it also bypasses the existing wired infrastructure and legacy service providers (i.e. the phone and cable companies). This book provides a basic technical introduction to the IEEE standard, allowing engineers, technologists, and decision-makers to ascertain how this hugely disruptive technology is going to affect their businesses